Multimodality imaging for the diagnosis and treatment of constrictive pericarditis. (2nd September 2019) - Chetrit, Michael; Natalie Szpakowski, Natalie; Desai, Milind Y.
ABSTRACT: Introduction : Constrictive pericarditis can result in debilitating congestive right heart failure and has been considered an important cause of morbidity and mortality in patients with cardiovascular disease. Multimodality imaging continues to play a fundamental role in the individual approach to diagnosis, management, and prognosis of patients with this clinical syndrome. Areas covered : This article gives an overview of the clinical spectrum of constrictive pericardial diseases and the role of multimodality imaging in the diagnosis of constrictive pericarditis. There is a focus on the emerging role of cardiac magnetic resonance (CMR) for the diagnosis, management, and prognostication of patients with constrictive pericarditis based on more recent case series, retrospective and prospective studies, which have helped to define the role of CMR. Expert opinion : Advanced multimodality imaging assists with identification of both overt and subclinical pericardial inflammation. This allows the pericardiologist to recognize patients with potentially reversible disease, trial medical therapy, and thereby avoid mechanical removal of the pericardium. Further, pericardial characterization by CMR has provided novel information about the natural history of these pericardial conditions, which can help tailor therapy and improve prognosis.